A rapid, easy and economical method for assay of drug resistance in Neurospora - K. D. MUNKRES (Fungal Genetics Reports, 1990)
Assay of bacterial drug resistance with linear concentration diffusion gradient plates was first described by Szylbalski (1952 Science 116:46-51). We have applied the method to Neurospora.